Sediments, Morphology and Sedimentary Processes on Continental Shelves : Advances in Technologies, Research and Applications - Li, Michael Z.; Sherwood , Christopher R.; Hill, Philip R. (West Sessex : Wiley-BlackWell, 2012)
The application of multibeam and sediment transport measurement technologies and the adoption of multi-faceted research methodologies have greatly advanced our understanding of the sedimentary processes on continental shelves in the last decade.This book uniquely blends cutting-edge research and state-of-the art review articles that take stock of new advances in multibeam mapping and sediment transport technologies, spatial analysis and modelling, and the applications of these advances to the understanding of shelf sediments, morphodynamics, and sedimentary processes. Case studies are also presented to illustrate the utilization of seabed property and process knowledge in habitat mapping and ocean management With its mix of papers focusing on technological advances, integration of shelf morphology and processes, and the application of these advances to coastal and ocean management, this Special Publication volume will serve as a milestone reference for professional marine scientists and as advanced text for students in marine geology, sedimentology and oceanography.
Includes bibliographical references.; List of reviewers 417-418p.; Index 419-432p.
Keywords: Continental margins; Sediment transport; Sedimentation and deposition; Sedimentology; Geology